Pengaruh Dinasti Abbasiyah Terhadap Kemajuan Peradaban Islam - Zaitun, Arifah (Universitas Cokroaminoto Yogyakarta, 2024)
The Abbasid dynasty was established from 750 to 1258 AD. The Abbasid dynasty was founded on dissatisfaction with the Umayyad dynasty, and reached its peak under the leadership of Caliphs Harun Al-Rashid and Al-Ma'mun, characterized by economic prosperity, political stability, and scientific advancement. Important figures such as Al-Khwarizmi and Ibn Sina made major contributions in various fields of science. The collapse of the dynasty was caused by a combination of internal factors such as internal conflicts and corruption, external factors such as Mongol attacks, research using the literature study method. The results showed that the Abbasid dynasty played a crucial role in the history of Islamic civilization, with significant contributions in science, education, economy, and culture. Although it has collapsed, its memory and impact remain to this day.